Patient Satisfaction of Service and Availability of Medical and Drugs among Inpatient Hospital West Sulawesi - Wita Oileri Tikirik; Amir Imbaruddin (Alta Dharma Publisher, 2021)
This study discusses how patient satisfaction with services and availability of medical facilities and medicines in the inpatient unit of the West Sulawesi Provincial Hospital, in terms of indicators of completeness of medical equipment and laboratory services so that they do not need to be sent to other hospitals, indicators of the availability of medicines in hospital pharmacy, indicator of length of service time at hospital dispensary and indicator of service for hospital dispensary officers. The method used in this research is descriptive method with quantitative approach. The population in this study were 2874 patients treated at the West Sulawesi Provincial Hospital. The sample in this study using accidental sampling technique, so that samples of this study amounted to 97 people. Data collection techniques used in this study questionnaires, interviews, review of documents and documentation. Data analysis using frequency distribution tables and percentage analysis. The results showed that the percentage of patient satisfaction with the service and availability of medical facilities and medicines in the inpatient unit of the West Sulawesi Provincial Hospital in terms of indicators of completeness of medical equipment and laboratory services, so there was no need to be sent to other hospitals by 66.2%, indicator the availability of medicines in hospital dispensaries was 67.4%, the indicator of length of service time at hospital dispensaries was 76.1% and the indicator of service for hospital dispensaries was 75.7%. Dan hasil perhitungan persentase seluruh item indikator diperoleh nilai rata-rata skor sebesar 71,3%. Secara keseluruhan pelayanan dan ketersediaan sarana medis dan obat-obatan di unit rawat inap RSUD Provinsi Sulawesi Barat sudah dapat memenuhi harapan pasien. And the results of calculation of the percentage indicator of all items obtained average value score of 71.3%. Overall the service and the availability of medical facilities and medicines in the hospital inpatient units of West Sulawesi province has been able to meet the expectations of patients.